ZINC STRESS ALLEVIATION BY SALICYLIC ACID IN HAIRY WILLOWHERB (Epilobium hirsutum L.) UNDER IN VITRO CONDITIONS - Akin, Betul; Bingol, Nuket A.; Kocacaliskan, Ismail (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2022)
Salicylic acid (SA) is recognized as an exogenous plant growth regulator involved in the regulation of important plant physiological processes. Zinc (Zn) stress alleviation by SA in Epilobium hirsutum under in vitro conditions was tested in this study. Primarily, seeds were pre-treated with 0, 0.1, and 0.5 mM SA and exposed to the different Zn concentrations in Murashige and Skoog medium (MS). The shoot tips of plants germinated in a medium containing 0.5 mM SA+10 mg/L Zn were used in shoot multiplication. Secondly, the shoot explants of E. hirsutum cultures were also successfully established in MS medium with 1 mg/L thidiazuron (TDZ)+0.5 mg/L Indole-3 Butyric Acid (IBA). Finally, sterile plantlets were gradually transferred to the hydroponic culture. Zn accumulation of seedlings was the highest in 75 mg/L Zn solutions (13.558.90 mg/kg dry weight (DW)). The high concentration of Zn (75 mg/L) significantly increased the chlorophyll content of the leaves. There was a significant decline in the activity of carbonic anhydrase (CA) in both leaves and roots of seedlings grown under increasing Zn concentrations. The activity of the polyphenol oxidase (PPO) enzyme increased with increasing Zn concentrations in hairy-willowherb. Compared with other concentrations, 75 mg/L Zn had a positive effect on PPO activities in both root and leaf tissues of the plant.
Keywords: Enzyme activities; Epilobium hirsutum; photosynthetic pigments; salicylic acid; tissue culture; zinc; TISSUE-CULTURE; CARBONIC-ANHYDRASE; PLANT; PHYTOREMEDIATION; TOLERANCE; CADMIUM; ACCUMULATION; GROWTH; SELECTION; WETLAND; Environmental Sciences & Ecology